Whole-transcriptome analysis of atrophic ovaries in broody chickens reveals regulatory pathways associated with proliferation and apoptosis - Lingbin Liu (Nature Portfolio, 2018)
Abstract Broodiness in laying hens results in atrophy of the ovary and consequently decreases productivity. However, the regulatory mechanisms that drive ovary development remain elusive. Thus, we collected atrophic ovaries (AO) from 380-day-old broody chickens (BC) and normal ovaries (NO) from even-aged egg-laying hens (EH) for RNA sequencing. We identified 3,480 protein-coding transcripts that were differentially expressed (DE), including 1,719 that were down-regulated and 1,761 that were up-regulated in AO. There were 959 lncRNA transcripts that were DE, including 56 that were down-regulated and 903 that were up-regulated. Among the116 miRNAs that were DE, 79 were down-regulated and 37 were up-regulated in AO. Numerous DE protein-coding transcripts and target genes for miRNAs/lncRNAs were significantly enriched in reproductive processes, cell proliferation, and apoptosis pathways. A miRNA-intersection gene-pathway network was constructed by considering target relationships and correlation of the expression levels between ovary development-related genes and miRNAs. We also constructed a competing endogenous RNA (ceRNA) network by integrating competing relationships between protein-coding genes and lncRNA transcripts, and identified several lncRNA transcripts predicted to regulate the CASP6, CYP1B1, GADD45, MMP2, and SMAS2 genes. In conclusion, we discovered protein-coding genes, miRNAs, and lncRNA transcripts that are candidate regulators of ovary development in broody chickens.